1996
DOI: 10.1029/96jb02488
|View full text |Cite
|
Sign up to set email alerts
|

Global Positioning System constraints on fault slip rates in southern California and northern Baja, Mexico

Abstract: We use Global Positioning System (GPS) estimates of horizontal site velocity to constrain slip rates on faults comprising the Pacific-North America plate boundary in southern California and northern Mexico. We enlist a simple elastic block model to parameterize the distribution and sum of deformation within and across the plate boundary. We estimate a Pacific-North America relative plate motion rate of 49 _+ 3 mm/yr (one standard deviation), consistent with NUVEL-1A estimates. We are able to resolve robust sli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
193
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 188 publications
(204 citation statements)
references
References 48 publications
(25 reference statements)
9
193
1
Order By: Relevance
“…This, in turn, suggests a complex kinematic evolution, which may explain apparent discrepancies between slip rate estimates obtained from geologic and geodetic data. Our results are at odds with combined InSAR and GPS data, which suggest much higher slip rates for the southern SJFZ [Fialko, 2006;Lundgren et al, 2009], but consistent with GPS block models, as well as elastic and viscoelastic models of crustal deformation in this region [Bennett et al, 1996;Meade and Hager, 2005;Becker et al, 2005;Fay and Humphreys, 2005]; the large differences of these geodetically derived slip rates may result from differences in modeling approaches, or temporal and spatial coverage of the geodetic data. Seismic hazard studies commonly rely on long-term Quaternary rates to infer short-term hazard.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…This, in turn, suggests a complex kinematic evolution, which may explain apparent discrepancies between slip rate estimates obtained from geologic and geodetic data. Our results are at odds with combined InSAR and GPS data, which suggest much higher slip rates for the southern SJFZ [Fialko, 2006;Lundgren et al, 2009], but consistent with GPS block models, as well as elastic and viscoelastic models of crustal deformation in this region [Bennett et al, 1996;Meade and Hager, 2005;Becker et al, 2005;Fay and Humphreys, 2005]; the large differences of these geodetically derived slip rates may result from differences in modeling approaches, or temporal and spatial coverage of the geodetic data. Seismic hazard studies commonly rely on long-term Quaternary rates to infer short-term hazard.…”
Section: Discussioncontrasting
confidence: 57%
“…The southern San Andreas and the San Jacinto fault zones are the two principal structures, together accommodating ∼35 mm/yr, that is ∼80%, of the Pacific-North America (PA-NA) relative plate motion in this region [King and Savage, 1983;DeMets and Dixon, 1999;Bennett et al, 1996;Fialko, 2006]. Geodetically derived slip rate estimates are on the order of 10-20 mm/yr for both of these fault zones, but only 2-6 mm/yr for the Elsinore fault zone [Johnson et al, 1994;Bennett et al, 1996;Meade and Hager, 2005;Becker et al, 2005;Fay and Humphreys, 2005].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inversions of geodetic and seismic data indicated that the slip at depth in the northern part of both events were somewhat higher than the surface values, about a meter for the 1940 and about half that for the 1979 event, but the deep slip at the southern end is similar to the surface displacement profile [King and Thatcher, 1998]. The potential slip accumulated on the Imperial fault between 1940 and 1979 is shown by the horizontal line, based on the estimate of 35 ± 2 mm/yr from GPS data [Bennett et al, 1996]. Hence the 1940 stress-drop had by 1979 been recovered in the northern end of the rupture but not in the southern end; the slip deficit there indicating that a residual stress-drop existed in that region in 1979.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have attempted to estimate the contemporaneous slip rates on the southern SAF system by fitting elastic halfspace models to rather sparse ground-based geodetic measurements from a dozen of monuments spanning a ∼100 km long profile across the fault 8,9 . Also, InSAR (Interferometric Synthetic Aperture Radar) data collected in the near field of the geologically mapped fault trace were used to detect the presence and extent of fault creep 4 .…”
mentioning
confidence: 99%